Sphingomyelin synthase 2 is a positive regulator of the CSF1R-STAT3 pathway in pancreatic cancer-associated macrophage - He, Shuhua; Gu, Xiang; Yang, Jintong; Xu, Fei; Hu, Jiachun; Wang, Wei; Huang, Yiheng; Lou, Bin; Ding, Tingbo; Zhou, Lu; Ye, Deyong; Yu, Ker; et al. (Frontiers in Pharmacology, 2022)
Background: Tumor-associated macrophages (TAMs) are one of the most abundant immune cells in the pancreatic cancer stroma and are related to the poor prognosis of pancreatic ductal carcinoma (PDAC) patients. Therefore, targeting TAMs is a possible strategy for the treatment of pancreatic cancer. Purpose: We would like to investigate the role of sphingomyelin synthase 2 (SMS2) and the effect of the SMS2 selective inhibitor YE2 in TAMs and the pancreatic tumor microenvironment. In addition, we also would like to investigate the mechanism by which YE2 attenuates macrophage M2 polarization. Methods: YE2 was utilized to treat macrophages (in vitro) and mice (in vivo). Western blotting and real-time PCR were used to detect the protein levels and mRNA levels of macrophage M2 polarization markers and their downstream signaling pathways. SMS2 gene knockout (KO) mice and their controls were used to establish a PANC-02 orthotopic pancreatic cancer model, and immune cell infiltration in the tumor tissue was analyzed by immunohistochemistry (IHC). Results: We found that SMS2 mRNA expression is positively correlated with TAMs, the immunosuppressive microenvironment, and poor prognosis in PDAC patients. SMS2 deficiency was confirmed to have an inhibitory effect on the growth of orthotopic PANC-02 tumors in vivo. The deficiency not only reduced the infiltration of TAMs but also regulated other immune components in the tumor microenvironment. In tissue culture, YE2 inhibited M2 polarization in both bone marrow-derived macrophages (BMDMs) and THP-1 macrophages and eliminated the protumor effect of M2 macrophages. In the mouse model, YE2 treatment reduced the infiltration of TAMs and regulated other immune components in the tumor microenvironment, slowing the progression of PANC-02 tumors. In terms of mechanism, we found that the inhibition of SMS2 could downregulate the expression of IL4R and CSF1R, thereby attenuating M2 polarization. Conclusion: The SMS2 inhibitor YE2 or SMS2 deficiency can prevent macrophage M2 polarization in pancreatic cancer, and SMS2 could be a new potential target for the treatment of pancreatic cancer.